Strategi Adaptasi Organisasi: Studi Kasus Transformasi Digital pada Perusahaan Manufaktur - Arief Saptono; Devi Lestari (Journal of Economics, Management, and Accounting, 2026)
This study examines organizational adaptation strategies in digital transformation within manufacturing firms through a qualitative interpretative library research design grounded in a critical constructivist epistemology. Drawing on systematically selected and thematically synthesized scholarly literature, the analysis integrates operational, structural, leadership, and human resource perspectives to explain how organizations respond to digital disruption. The findings demonstrate that successful digital transformation depends on the coherence between adaptive operational practices, flexible organizational structures, digitally oriented leadership, and continuous workforce capability development. Fragmented or technocentric approaches are shown to generate limited performance gains and organizational resistance. The study further highlights the relevance of dynamic capability theory in explaining how sensing, seizing, and reconfiguring processes enable sustainable adaptation. By synthesizing diverse empirical and conceptual contributions, this article advances an integrative framework that clarifies the mechanisms linking digital transformation and organizational performance in manufacturing contexts. Methodologically, the study contributes by offering a transparent and replicable approach to theory-driven literature synthesis.